2007
DOI: 10.1073/pnas.0609299104
|View full text |Cite
|
Sign up to set email alerts
|

Human prostate epithelium lacks Wee1A-mediated DNA damage-induced checkpoint enforcement

Abstract: Cellular DNA damage triggers the DNA damage response pathway and leads to enforcement of cell cycle checkpoints, which are essential for the maintenance of genomic integrity and are activated in early stages of tumorigenesis. A special feature of prostate cancer is its high incidence and multifocality. To address the functionality of DNA damage checkpoints in the prostate, we analyzed the responses of human primary prostate epithelial cells (HPECs) and freshly isolated human prostate tissues to ␥-irradiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 29 publications
3
63
0
Order By: Relevance
“…Cyclin D1, cyclin E, CDK4 and CDK6 are also critical regulators of G1 progression and G1-S transition (33). Inhibition of cyclin D1, cyclin E and CDK4 activation blocks G1-S transition in the cell cycle (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclin D1, cyclin E, CDK4 and CDK6 are also critical regulators of G1 progression and G1-S transition (33). Inhibition of cyclin D1, cyclin E and CDK4 activation blocks G1-S transition in the cell cycle (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…The INK4 families can bind to CDK4 and/or to CDK6 and inhibit the catalytic activity of the CDK/cyclin D complex (28)(29)(30)(31). Cyclin D1, cyclin E, CDK4 and CDK6 are also critical regulators of G1 progression and G1-S transition (33). Inhibition of cyclin D1, cyclin E and CDK4 activation blocks G1-S transition in the cell cycle (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, analysis of normal and malignant cell lines in their propensity to undergo p53 and MDM2 nucleolar localization following proteasome inhibition showed that the response was irrespective of tissue type or pathological status of the cells (Supplementary Table S1). Furthermore, treatment of ex vivo cultured human prostate tissues (Kiviharju-af Ha¨llstro¨m et al, 2007) with MG132 led to the formation of p53 aggregates in epithelial cells of the prostate gland, indicating that the aggregate formation is not only an artifact of cells cultured in monolayer, but is also observed in the context of normal tissue architecture (Supplementary Figure S1d).…”
Section: Proteasome Inhibition Alters Nucleolar Morphologymentioning
confidence: 99%
“…Downregulation of the WEE1 protein was also observed in pituitary adenomas, and this was also associated with miRNA expression (Butz et al, 2010). Moreover, prostate epithelium, which is prone to prostate cancer development, also expressed very low levels of WEE1 (Kiviharju-af Hallstrom et al, 2007). Based on our studies (Beck et al, 2010), low levels of WEE1 during human tumorigenesis would likely lead to deregulated replication with subsequent spontaneous DNA damage in S phase.…”
Section: Cancer-associated Downregulation Of Wee1mentioning
confidence: 95%